Single-Cell RNA Sequencing in Human Retinal Degeneration Reveals Distinct Glial Cell Populations - Andrew P. Voigt; Elaine Binkley; Miles J. Flamme-Wiese; Shemin Zeng; Adam P. DeLuca; Todd E. Scheetz; Budd A. Tucker; Robert F. Mullins; Edwin M. Stone (Cells, 2020)
Degenerative diseases affecting retinal photoreceptor cells have numerous etiologies and clinical presentations. We clinically and molecularly studied the retina of a 70-year-old patient with retinal degeneration attributed to autoimmune retinopathy. The patient was followed for 19 years for progressive peripheral visual field loss and pigmentary changes. Single-cell RNA sequencing was performed on foveal and peripheral retina from this patient and four control patients, and cell-specific gene expression differences were identified between healthy and degenerating retina. Distinct populations of glial cells, including astrocytes and Müller cells, were identified in the tissue from the retinal degeneration patient. The glial cell populations demonstrated an expression profile consistent with reactive gliosis. This report provides evidence that glial cells have a distinct transcriptome in the setting of human retinal degeneration and represents a complementary clinical and molecular investigation of a case of progressive retinal disease.